Emosi Tokoh dalam Novel Ayah dan Sirkus Pohon Karya Andrea Hirata - Hardianti, Fitriana; Pamungkas, Onok Yayang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study examines the classification of the emotions of characters in the novel Father and the Tree Circus by Andrea Hirata. The approach used is the approach of literary psychology. The method used in this study is descriptive qualitative. The data taken in this study is in the form of text excerpts that show the emotions of the characters. The source of the data in the study is the novel Father and the Tree Circus by Andrea Hirata. The data collection technique used is the library technique. The data validity technique uses theoretical triangulation techniques. The data analysis techniques used by researchers are, 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusions. Based on the results of the research conducted, there are eight classifications of emotions. The figures who dominate emotions are Hobirin, Sabari, and Marlena. Angry emotions are experienced by Marlena who is depicted through action by yelling at Sabari when handing over Marlena's fallen handkerchief. The delight experienced by Hobirin when he was accepted into the job of being a traveling circus. Sadly portrayed through the character of Hobirin when the work of the traveling circus is temporarily suspended. Guilt is clearly portrayed by the author through the character Hobirin who feels guilty to his father for doing bad things until he is taken to the police station. Fear is portrayed through the character Sabari who previously felt scared after a divorce case with his wife. Hate is felt by Hobirin who is depicted when the character hates the pomegranate tree. Love is portrayed through Sabari's actions as he grasps a pencil given by Marlena. Shame is experienced by Hobirin which is depicted when he feels ashamed of himself when he loses his job. An important implication of this research is that literature can contribute to the discussion of psychological science.Keywords: Emotions, Psychology, Novel, Ayah dan Sirkus Pohon, Andrea Hirata.